Financial evaluation of the Santa Ana Hunting Reserve - de la Vega Mena, Anel; Sangerman-Jarquín, Dora Ma.; García Salazar, José Alberto; Navarro Bravo, Agustín; Damián Huato, Miguel Ángel; de Rindermann, Rita Schwentesius (Revista Mexicana de Ciencias Agrícolas, 2018)
This investigation was focused on the experience of the Santa Ana Hunting Reserve, since it has led its operation to the integral use and conservation of its resources, with a diversification of activities such as sport hunting and breeding and training of hunting dogs. The financial feasibility was analyzed in two parts. For the first one, a 10-year projection was made, contemplating the lease contract that the reserve has, and in the second one, the same projection was made for 20 years, since the construction of the building and the fence are the most important item in this project. Both parts had two scenarios: in the first, we used the investment costs of 2007 and operating costs from 2007 to 2008, and in second place, we looked at it as though investment had begun in 2007. With an updating rate of 12% the indicators obtained (current net value, cost: benefit ratio, benefit: net investment ratio, and internal profitability rate) in both parts, and with both scenarios, showed that the reserve is financially feasible. Another important aspect was determining travel costs, i.e., the total amount of expenses incurred into from the place of residence to the cost of a house. The total for this was MX $ 96 236 pesos for 350 people a year, indicating an indirect revenue that the reserve generates.
Keywords: conservation; natural resources; financial feasibility